2005
DOI: 10.1099/mic.0.27758-0
|View full text |Cite|
|
Sign up to set email alerts
|

Secondary metabolites from endophytic Streptomyces aureofaciens CMUAc130 and their antifungal activity

Abstract: Streptomyces aureofaciens CMUAc130 was isolated from the root tissue of Zingiber officinale Rosc. (Zingiberaceae). It was an antagonist of Colletotrichum musae and Fusarium oxysporum, the causative agents of anthracnose of banana and wilt of wheat, respectively. Evidence for the in vitro antibiosis of S. aureofaciens CMUAc130 was demonstrated by the zone of fungal-growth inhibition. Microscopic observations showed thickness and bulbous structures at the edges of the inhibited fungal hyphae. The culture filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 15 publications
3
81
0
4
Order By: Relevance
“…Fungal culture broth (200 lL) was transferred to an Oxford cup (6 9 7.8 9 10 mm) to screen antifungal activity against three common pathogenic fungi -F. graminearum, Sclerotinia sclerotiorum and Phytophthora capsici according to the method reported by Taechowisan et al, (2005). Briefly, fungi blocks (5 mm in diameter) were made with a cork borer from the edge of the fresh fungi cultured on PDA medium and subsequently placed in the central of new PDA culture plates, cultivating at 25°C.…”
Section: Agar Diffusion Methodsmentioning
confidence: 99%
“…Fungal culture broth (200 lL) was transferred to an Oxford cup (6 9 7.8 9 10 mm) to screen antifungal activity against three common pathogenic fungi -F. graminearum, Sclerotinia sclerotiorum and Phytophthora capsici according to the method reported by Taechowisan et al, (2005). Briefly, fungi blocks (5 mm in diameter) were made with a cork borer from the edge of the fresh fungi cultured on PDA medium and subsequently placed in the central of new PDA culture plates, cultivating at 25°C.…”
Section: Agar Diffusion Methodsmentioning
confidence: 99%
“…Remya and Vijayakumar (2008) reported that ethyl acetate extract of Streptomyces strain RM42 showed maximum activity against Escherichia coli followed by Salmonella typhi, Stphylococcus aureus, Candida albicans and Bacillus subtilis. Similarly, the extraction of antibiotics has been carried out from actinomycetes by using various solvents including ethyl acetate and methanol (Taechowisan et al 2005;Ilic et al 2005;Saha et al 2005).…”
Section: Partial Purification Of Antibiotic Metabolitementioning
confidence: 99%
“…The medium (200 ml in 500 ml Erlenmeyer flask) was inoculated with 5 ml of homogenous bacteria suspension (620 nm, 0.08 O.D.) and incubated at 30°C on a rotary shaker (120 rpm) for five days (Taechowisan et al 2005). The Streptomyces sp.…”
Section: Screening Of Actinomycetales For Antimicrobial Activitymentioning
confidence: 99%